Fixed Point Theorems in Soft Multiplicative Metric Space - Rathee, Savita; Girdhar, Ridam; Dhingra, Kusum (Communications in Mathematics and Applications, 2020)
In this article, we first define the concept of soft multiplicative metric space and then establish its relation with soft metric and multiplicative metric space. This new approach enables us to obtain some fixed point results. We also provide some examples to verify and illustrate our results.
Keywords: Soft set; Soft point; Soft real number; Soft metric space; Soft multiplicative metric space